“THE RELATIONSHIP BETWEEN STUDENT’S SELF-ESTEEM AND STUDENT’S SPEAKING ABILITY OF THE TENTH GRADE AT SMK MUHAMMADIYAH 3 GEMOLONG - Sulistiawati Sulistiawati; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2020)
The present study entitled the relationship between student’s self-esteem and student’s speaking ability of the tenth grade at SMK Muhammadiyah 3 Gemolong. The aim of the study was to investigate whether there is significant relationship between student’s self-esteem and and student’s speaking ability of the tenth grade students at SMK Muhammadiyah 3 Gemolong. The data were obtained by the quantitative method in correlational design.””” The study was conducted at SMK Muhamadiyah 3 Gemolong. The population were 147 students of the tenth grade at SMK Muhammadiyah 3 Gemolong in 2019/2020 academic year. The tenth grade consisted of 6 classes. The study applied random sampling technique. The sample were 22 students. The instrument to collect the data of two variables were self-esteem questionnaire and oral test of speaking ability. The questionnaire used Coopersmith’s self-esteem scale that contained of 37 valid questions and the rubric of oral test to measure speaking ability based Penny Ur. The analyzing of data used SPSS 22.””” The findings of study were the tenth grade students of SMK Muh 3 Gemolong had 50% in high self – esteem with the mean score 65.86 and their speaking ability were in adequate level 36% with the mean score 68.63. The coefficient relationship (rxy) 0.943. Based on the result of the study, it could be concluded that the self-esteem had high positive relationship with the speaking ability of the tenth grade students at SMK Muhammadiyah 3 Gemolong.”” Keywords: self-esteem, speaking ability, correlation study